PEMAKNAAN JIHAD BAGI ANGGOTA FPI RIAU DALAM AKSI SUPER DAMAI 212 DI JAKARTA - Masithoh, Dewi; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Islamic Defense Action volume III (Aksi Super Damai 212) on December 2, 2016 in Monas Jakarta followed by Muslims from all over Indonesia became a historic event for the nation. Action backdrop of religion by the Governor of DKI Jakarta. The action led by GNPF-MUI with the theme